Estimation of Fertility Levels and Trends in Nepal - Thasineku, Om Chandra (JMC Research Journal, 2019)
The objectives of this study are to estimate and analyze levels and trends of fertility by indirect methods, to verify the estimated level of fertility from indirect methods by linear regression method and to compare the estimated level of fertility from indirect methods with direct method. The source of data for this study is secondary which is obtained from data files of Nepal Demographic and Health Surveys of the years 2006, 2011 and 2016. Required data to estimate fertility level (TFR) is obtained by using IBM SPSS Statistics 21. Two indirect methods were used in this study i.e. comparing period fertility rates with average parities for a hypothetical cohort and Arriaga method. The data were tabulated manually and estimated by Excel Sheet and MORTPAK. For verification of estimated value on level of fertility (TFR), linear regression was used. Estimation of fertility levels (TFRs) at the national level by indirect methods and linear regression are almost same which show the high accuracy of estimation of fertility by indirect methods at the national level. Similarly, comparison of estimated trend of fertility (TFR) by indirect methods with direct method is almost same at the national level. So, estimation of fertility level (TFR) by indirect methods is found suitable at the national level.